2010
DOI: 10.1186/1471-2474-11-194
|View full text |Cite
|
Sign up to set email alerts
|

Validity and test-retest reliability of manual goniometers for measuring passive hip range of motion in femoroacetabular impingement patients.

Abstract: BackgroundThe aims of this study were to evaluate the construct validity (known group), concurrent validity (criterion based) and test-retest (intra-rater) reliability of manual goniometers to measure passive hip range of motion (ROM) in femoroacetabular impingement patients and healthy controls.MethodsPassive hip flexion, abduction, adduction, internal and external rotation ROMs were simultaneously measured with a conventional goniometer and an electromagnetic tracking system (ETS) on two different testing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
174
5
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(198 citation statements)
references
References 45 publications
11
174
5
8
Order By: Relevance
“…In the literature, interobserver reliability of visual (not goniometric) measurement of hip ROM was found to be moderate (intraclass correlation coefficient (ICC) 0.48-0.56) [19]; another study calculated a goniometer internal rotation ICC of 0.48 [20]. Intraobserver reliability of the goniometer on the other hand proved excellent and similar to that of an electromagnetic tracking system: ICC for internal rotation was 0.95 and standard error (SEM) was 2.4°; flexion had the highest SEM (3.9°), concurrent validity was good [21]. Although we did not perform a reliability assessment on our data, we estimate our standard measurement error to be at least 4°.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, interobserver reliability of visual (not goniometric) measurement of hip ROM was found to be moderate (intraclass correlation coefficient (ICC) 0.48-0.56) [19]; another study calculated a goniometer internal rotation ICC of 0.48 [20]. Intraobserver reliability of the goniometer on the other hand proved excellent and similar to that of an electromagnetic tracking system: ICC for internal rotation was 0.95 and standard error (SEM) was 2.4°; flexion had the highest SEM (3.9°), concurrent validity was good [21]. Although we did not perform a reliability assessment on our data, we estimate our standard measurement error to be at least 4°.…”
Section: Discussionmentioning
confidence: 98%
“…This is even higher than the mean value of hip flexion in our normal group. An explanation for this discrepancy might be the unrecognized concomitant lumbar lordosis [14,19,28] and compensatory external rotation of the hip [7]. The only concise statement in terms of ROM refers to a limited rotation in flexion and/or extension and abduction [31].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we selected a target bar height of 20°of hip flexion from a sitting position. Although the possible range of motion of flexion in the supine position has been stated to be 120° [14,15], there is no reported study of the hip flexion range in a sitting posture for performing functional activities. Previous kinematic studies have demonstrated that high hip flexion, i.e., 95-114°, occurs in daily activities such as sitting with legs crossed, squatting, and putting on socks, in asymptomatic subjects [16,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The normal angle of hip flexion is 120°in healthy people performing functional activities [14,15], and hip flexion flexibility is required to perform many daily activities, such as squatting, putting on shoes and socks, and riding a bicycle [16][17][18][19]. Since the hip joint and lumbar spine are both adjacent to the pelvis, the hip joint moves in cooperation with the lumbar spine to provide functional movement [20][21][22].…”
Section: Introductionmentioning
confidence: 99%